KINERJA PERUSAHAAN DITINJAU DARI STRUKTUR MODAL, UKURAN PERUSAHAAN DAN AGENCY COST SEBAGAI INTERVENING VARIABEL - Febriani, Tika Arizona (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
The purpose of this study is to determine the effect of capital structure and firm size on company performance, with agency cost as an intervening variable, in the food and beverage sector companies listed on the Indonesia Stock Exchange during the period 2014 to 2018. This research is quantitative in nature, using a population of food and beverage sector companies listed on the IDX from 2014 to 2018, with a sample of 14 companies. Data analysis was conducted using descriptive statistics and multiple regression analysis, with data testing assisted by IBM SPSS 21 software. The results of this study indicate that capital structure, firm size, and agency cost together affect company performance. Capital structure and firm size jointly have a significant effect on agency cost. Capital structure has a negative and significant effect on agency cost, while firm size does not have a significant effect on agency cost. Capital structure has a positive and significant effect on company performance. Firm size does not have a significant effect on company performance, and agency cost has a negative and significant effect on company performance.